Impact of crisis intervention on mental health in the context of specific civilian emergencies - Xiaoshan Hu; Jihua Liu; Bingyu Hao; Yang Lv (PLoS ONE, 2025)
Background The implementation of crisis response strategies, such as natural hazards, pandemics, and conflicts, is necessary during times of emergency. Despite the importance of these interventions, mental health outcomes in emergency situations remain poorly understood. There is a lack of research on the comparative effectiveness of different interventions. Therefore, this study addresses the following question: “How do crisis interventions affect mental health outcomes in emergencies?”. Methods This study aims to conduct a scoping review of the impact mechanisms of crisis intervention on the mental health of witnesses or participants in the context of emergencies. The study encompassed a wide array of studies, emphasizing the efficacy of several crisis intervention modalities, such as psychological first aid and trauma-focused therapy. Results Most of the existing results were based on hospitals, schools and communities as research scenarios. The findings revealed substantial beneficial effects on mental health outcomes, such as decreased symptoms of posttraumatic stress disorder (PTSD), anxiety, and depression. Nevertheless, discrepancies in the efficacy were observed depending on the nature of the emergency, the model of intervention, and the demographic variables. The study highlights the intricate nature of executing crisis interventions during emergencies, taking into account aspects such as cultural sensitivity, resource availability, and the necessity for customized approaches. Conclusion Crisis interventions are crucial in reducing the detrimental effects on mental health caused by emergencies. However, additional focused and enduring investigations are necessary to understand their efficacy in various emergency scenarios and demographics. Therefore, future research can further enrich psychological crisis intervention methods and deepen research on the impact of crisis intervention on mental health.